1970
DOI: 10.3329/bjsir.v42i4.747
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical and Biological Aspects of Monsoon Waters of AShulia for Economic and Aesthetic Applications: Preliminary Studies

Abstract: In the north-eastern part of Dhaka the 'Turag River' extends over Ashulia thana with a few branches. The north-eastern part of Ashulia thana mainly constitute low lands with a physiography of Madhupur Tract interlaced with Brahmaputra Floodplain. Monsoon extends over these lands from May to October and from July to October these lands remain flooded with a water depth of more than 180 cm to less than 275 cm due to surface runoff of rain water and overflow of the river canals. The area under water during this f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
(5 reference statements)
2
10
0
Order By: Relevance
“…During the monsoon period the concentration of TP had been increasing in the reservoirs due to intense rainfall, and a decreased concentration of TN is due to higher dilution [36]. The same scenario is being frequently observed in other tropical and subtropical Asian reservoirs, including those of Bangladesh [37], India [38], Nepal [39], and Sri Lanka [40].…”
Section: Introductionmentioning
confidence: 58%
“…During the monsoon period the concentration of TP had been increasing in the reservoirs due to intense rainfall, and a decreased concentration of TN is due to higher dilution [36]. The same scenario is being frequently observed in other tropical and subtropical Asian reservoirs, including those of Bangladesh [37], India [38], Nepal [39], and Sri Lanka [40].…”
Section: Introductionmentioning
confidence: 58%
“…The collected surface water samples from the Turag river contained significant amount of Cu and ranged from 0.01-0.02, 0.02-0.03 and 0.21-0.27mg/l during postmonsoon, pre-monsoon and monsoon season, respectively (Meghla et al, 2013) which is almost similar to the present study. The concentration of Cu ranged from 0.028-0.043mg/l at Ashulia point in the Turag River during the period from July to October (Khan et al, 2007). ISSN 1999-7361 The study revealed that the highest concentration of zinc (Zn) in beel water was 0.79mg/l at sampling St-1 in April while the lowest was 0.56mg/l at St-3 in February (Fig.…”
Section: Heavy Metals Concentration In Watermentioning
confidence: 95%
“…The temperature ranged from 22.9-36.0ºC along the Shitalakhya river in dry season during the sampling period where higher temperature was April, compared to February and March due to high air temperature (Alam et al, 2006), which is almost similar to the present study. The temperature ranged from 24.6-28.2ºC at Ashulia point in the Turag river during the period from July to October (Khan et al, 2007).…”
Section: Physicochemical Water Quality Parametersmentioning
confidence: 99%
“…None of these three heavy metals, Arsenic (As), Lead (Pb) and Iron (Fe) were detected in both pond and jar water, but iron was detected in six samples in tube-wells where only one was positive to arsenic ( Figure 9). But Lead (Pb) and Iron (Fe) were detected in pond water by another study conducted in Ashulia area, Bangladesh [50]. A recent study showed that arsenic was not detected in jar water of Dhaka city but iron was in acceptable limit [49].…”
Section: Presence Of Heavy Metalsmentioning
confidence: 99%